TSUNAMI DISASTER VULNERABILITY ANALYSIS USING GEOGRAPHIC ANALYSIS SYSTEM (GIS) IN PACITAN DISTRICT, EAST JAVA - Marceyl, Ronald; Yuda Anwari, Ade; Sufyan, Adi; Jalaludin, Muzani (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2025)
Tsunami risk monitoring and management planning have become mandatory for the management of Pacitan District due to the high tsunami risk in the region caused by being among the subduction zone of the major plates and an area of active megathrust and ocean floor expansion. Approach in this study used four dimensions of risk to develop a tsunami index value: physical, social, economic, and environmental. The enumeration exercise used secondary data and analysis and processing techniques using QGIS and Microsoft Excel software, with the specific aim of graphically presenting the studied areas of tsunami vulnerability and the vulnerability index score from the regions for editing purposes. The locations such as Pacitan, Pringkuku, and Tulakan sub-districts are relatively vulnerable and therefore need to be upgraded its underdeveloped areas. This is because of poor infrastructure, population congestion, and unwarranted socioeconomic circumstances leading to a high level of exposure. Where such risks exist there is the need for planning such vulnerable areas according to the level to minimize the high risk of tsunami vulnerability in Pacitan. Keywords: Disaster Risk Assessment, Geographic Information Systems (GIS), Tsunami Vulnerability